8-Chloro-6-iodo-2-phenylchromeno 4,3-c pyrazol-4(2H)-one N,N-dimethylformamide monosolvate - Lokhande, P.; Ali, Hapipah Mohd; Khaledi, H.; Hasanzadeh, K. (International Union of Crystallography, 2011)
In the title compound, C16H8ClIN2O2 center dot C3H7NO, the fused tricyclic pyrazolocoumarin ring and the N-phenyl ring are almost coplanar, the dihedral angle between them being 1.86 (9)degrees. In the crystal, these rings stack on top of each other via pi-pi interactions [centroid-centroid distances = 3.489 (2), 3.637 (2), 3.505 (2) and 3.662 (2) angstrom], forming infinite chains along the a axis. The chains are connected into layers parallel to ac plane through I center dot center dot center dot O interactions [3.0011 (18) angstrom] between pairs of symmetry-related molecules. The DMF solvent molecules are C-H center dot center dot center dot O bonded to this network.